Measurement of forced convection subcooled boiling flow through a vertical annular channel with high-speed video cameras and image reconstruction. Issue 2 (1st February 2022) - Ui, Atsushi; Furuya, Masahiro; Arai, Takahiro; Shirakawa, Kenetsu
ABSTRACT: In order to develop models regarding subcooled boiling flow and its heat transfer, we conducted subcooled boiling experiments to investigate subcooled bubble formation and measured development process of the bubbles using a test loop with a vertical annulus flow path under atmospheric conditions. Two-phase flow parameters regarding subcooled boiling, such as instantaneous bubble velocity, turbulent velocity components, void fraction, onset of nucleate boiling (ONB) and onset of significant void (OSV), were obtained with two high-speed video cameras in high resolution in temporally and spatially. The identical bubbles were identified from the two video images taken by the high-speed video cameras, and the trajectories were reconstructed in three-dimensional. The instantaneous bubble velocities and turbulence velocity components regarding bubble transport were quantified with the trajectory data. It was observed that the bubbles were rising along the surface of the heater rod moved largely in the circumferential direction, and it was found from the result that velocity component for circumferential direction was enough large compared with that for radial direction.